The Role of Intellectual Capital to Fill the Missing Link in The Relationship Between Social Responsibility and Islamic Banking Performance in Indonesia - Pratama, Bima Cinintya; Makhrus, Makhrus; Innayah, Maulida Nurul (Universitas Muhammadiyah Semarang, 2023)
The purpose of this research is to analyse how Islamic banks in Indonesia performance using antecedents of their level of social responsibility and intellectual capital. In addition, the mediating role of IC in the connection between CSR and firm performance is examined. This study predicts that CSR strategies have the potential to enhance corporate IC, giving rise to a new type of IC called